Computer - Campbell-Kelly, Martin, author.
1 online resource
Keywords: "Computer: A History of the Information Machine traces the history of the computer and its unlimited, information-processing potential. Comprehensive and accessibly written, this fully updated fourth edition adds new chapters on the globalization of information technology, the rise of social media, fake news, and the gig economy, and the regulatory frameworks being put in place to tame the ubiquitous computer. Computer is an insightful look at the pace of technological advancement and the seamless way computers are integrated into the modern world. The authors examine the history of the computer including the first steps taken by Charles Babbage in the nineteenth century, and how wartime needs and the development of electronics led to the giant ENIAC, the first electronic computer. For a generation IBM dominated the computer industry. In the 1980s, the desktop PC liberated people from room-sized, mainframe computers. Next, laptops and smartphones made computers available to half of the world's population, leading to the rise of Google and Facebook, and powerful apps that changed the way we work, consume, learn, and socialize. The volume is an essential resource for scholars and those studying computer history, technology history, and information and society, as well as a range of courses in the fields of computer science, communications, sociology, and management"--